Role of Different Subpopulations of CD8+ T Cells during HIV Exposure and Infection - Gonzalez, Sandra Milena; Taborda, Natalia Andrea; Rugeles, María Teresa (Frontiers in Immunology, 2017)
During HIV infection, specific responses exhibited by CD8+ T cells are crucial to establish an early, effective, and sustained viral control, preventing severe immune alterations and organ dysfunction. Several CD8+ T cells subsets have been identified, exhibiting differences in terms of activation, functional profile, and ability to limit HIV replication. Some of the most important CD8+ T cells subsets associated with viral control, production of potent antiviral molecules, and strong polyfunctional responses include Th1-like cytokine pattern and Tc17 cells. In addition, the expression of specific activation markers has been also associated with a more effective response of CD8+ T cells, as evidenced in HLA-DR+ CD38− cells. CD8+ T cells in both, peripheral blood and gut mucosa, are particularly important in individuals with a resistant phenotype, including HIV-exposed seronegative individuals (HESNs), long-term non-progressors (LTNPs) and HIV-controllers. Although the role of CD8+ T cells has been extensively explored in the context of an established HIV-1 infection, the presence of HIV-specific cells with effector abilities and a defined functional profile in HESNs, remain poorly understood. Here, we reviewed studies carried out on different subpopulations of CD8+ T cells in relation with natural resistance to HIV infection and progression.